Railway and road infrastructure in the Belt and Road Initiative countries: Estimating the impact of transport infrastructure on economic growth - Wang, Chao; Lim, Ming K.; Zhang, Xinyi; Zhao, Longfeng; Lee, Paul Tae-Woo (Transportation research. Part A, Policy and practice, 2020)
•The impact of the railway and road infrastructure on economic growth is examined.•The data covers 65 BRI countries from 2007 to 2016.•Four spatial weight matrices are applied in the spatial econometrics.•Results show different impacts from the national and regional perspectives.•Policy implications for driving economic growth in BRI countries are presented. China’s Belt and Road Initiative (BRI) is one of the most ambitious infrastructure investment efforts in history, representing great potential for stimulating regional economic growth in Asia, Europe and Africa. This study collects cross-country panel data from 2007 to 2016 and investigates the impact of transport infrastructure (railway and road) on the economic growth in the BRI countries. First, a spatial-temporal characteristics analysis of transport infrastructure and economic growth is presented. Then, the global Moran’s I and the local Moran scatterplot are employed to test for possible spatial autocorrelations. Finally, both static and dynamic spatial models are utilized to empirically examine the impact of transport infrastructure on economic growth from the national and regional perspectives. The estimation results at the national level reveal that the transport infrastructure in the BRI countries plays an essential role in facilitating economic growth. Moreover, this study finds significantly positive spatial spillover effects of economic growth in the categories of geographical distance, economic distance, cultural distance, and institutional distance spatial weight matrices, i.e., shorter geographical distances and economic, cultural and institutional similarities among the BRI countries lead to mutual economic growth. The estimation results at the regional level indicate that the spatial spillover effects of transport infrastructure are significantly negative in East Asia-Central Asia and the Commonwealth of Independent States and in South Asia. On the contrary, the positive spatial spillover effect of transport infrastructure on economic growth is most pronounced in Central and Eastern Europe. This indicates the polarization effect in the initial stage of the lagging transport infrastructure and the diffusion effects after the transport infrastructure is mature. This study is valuable because it examines the impact of transport infrastructure on economic growth in the BRI countries. In addition, two policy suggestions for driving the regional economy in the BRI countries are given.